EFFICACY OF INJECTING INTRA-VITREAL MOXIFLOXACIN IN ACUTE POST-OPERATIVE ENDOPHTHALMITIS - Ahmad, Adnan; Rehman, Mubbashir (Journal of Ayub Medical College Abbottabad, 2023)
Intra-vitreal Vancomycin (IV-V) and ceftazidime (IV-C) are commonly in the treatment of acute post-operative endophthalmitis. But there are suboptimal responses in some cases due to the emergence of antibiotic resistant micro-organisms. Moxifloxacin is a wide range antibacterial drug that is available as an eye drops for topical use for different types of ocular infections including post-operative endophthalmitis. But it has not been explored extensively as an intra-vitreal drug for post-operative endophthalmitis. We unveiled its broad spectrum anti-bacterial properties by giving it as an intra-vitreal route of delivery so to see its efficacy in post-operative endophthalmitis case. A 65 years old diabetic male presented with acute painful loss of vision in his right eye 2 days following his cataract extraction with posterior chamber intraocular lens implantation (PC IOL). His visual acuity (VA) on presentation was just counting finger close to eye. Slim lamp examination (SLE) revealed swollen lids, discharge in the inferior conjunctival fornix, conjunctival redness and chemosis, hazy cornea, fibrinous exudate in AC along with hypopyon, there was marked vitritis with yellowish fundal glow apparent. The patient was injected with intra-vitreal moxifloxacin 0.5mg/0.2 ml, along with topical and oral antibiotics in combination with steroids. VA reached to 6/24 and follow-up at 4th week didn't show any of intra-ocular inflammatory changes on SLE. Intra-vitreal moxifloxacin mono-therapy is a better substitute to combination of vancomycin and ceftazidime due to its broad-spectrum coverage in acute post-operative endophthalmitis.